Implementation of The JKN Program Related to Patient Admission, Medical Data Processing, Reporting and JKN Funding at Murni Teguh Medan Hospital - Lina Njoto; Sri Lestari Ramadhani Nasution; Ermi Girsang (Eduvest - Journal of Universal Studies, 2025)
The National Health Insurance (JKN) program is a government initiative aimed at supporting comprehensive health development to ensure that all Indonesians have the right to good health. According to data obtained from BPJS Kesehatan and RS Murni Teguh Medan, the average waiting time for polyclinic services exceeds the national quality indicators, which requires outpatient waiting times should not exceed 60 minutes. This study aims to analyze the challenges in implementing the JKN program, specifically related to patient admission, medical data processing, reporting, and funding at RS Murni Teguh Medan. This is a qualitative descriptive research involving three key informants (Persons-in-Charge or PICs) and six supporting staff members from the Registration, Medical Records, and JKN Billing units. The research identified several challenges: Man: The registration unit's human resources do not meet the required qualifications, as staff should ideally have a medical records background, resulting in reporting issues. Materials: Patient files are incomplete for administrative processes. Machine: The applications used, such as MTHIS (Hospital Management Information System), Mobile JKN, V-Claim, DIVA, and Online Pharmacy, face operational issues, leading to inefficient medical data processing and reporting. Methods: Although procedures are aligned with the SOPs, issues remain include patient overcrowding at registration, outpatient service waiting times exceeding 60 minutes, issues with registration in executive polyclinics, self-registration issues at APM, service penalties, and semi-manual medical data processing and reporting. Markets: Patients have limited knowledge of using Mobile JKN application, and pending claims are still prevalent. Money: Prolonged use of outdated electronic meda reduces systems performance.